Bacterial migration along solid surfaces. - Harkes, G (1992)
An in vitro system was developed to study the migration of uropathogenic Escherichia coli strains. In this system an aqueous agar gel is placed against a solid surface, allowing the bacteria to migrate along the gel/solid surface interface. Bacterial strains as well as solid surfaces were characterized by means of water contact angle and zeta potential measurements. When glass was used as the solid surface, significantly different migration times for the strains investigated were observed. Relationships among the observed migration times of six strains, their contact angles, and their zeta potentials were found. Relatively hydrophobic strains exhibited migration times shorter than those of hydrophilic strains. For highly negatively charged strains shorter migration times were found than were found for less negatively charged strains. When the fastest-migrating strain with respect to glass was allowed to migrate along solid surfaces differing in hydrophobicity and charge, no differences in migration times were found. Our findings indicate that strategies to prevent catheter-associated bacteriuria should be based on inhibition of bacterial growth rather than on modifying the physicochemical character of the catheter surface.